Diagnostic imaging observations in cats treated with the subcutaneous ureteral bypass system. (8th October 2019) - Dirrig, H.; Lamb, C. R.; Kulendra, N.; Halfacree, Z.
Abstract : Objectives: To describe pre‐ and post‐operative ultrasonographic and fluoroscopic findings, including any abnormalities, in cats treated for ureteral obstruction with a subcutaneous ureteral bypass system. Methods: Retrospective review of imaging findings in cats with ureteral obstruction that had surgery to place the first version of the bypass system and at least one follow‐up ultrasound or fluoroscopic study. Pre‐ and post‐operative renal pelvic diameter on ultrasound, fluoroscopic appearance of the bypass system and any related abnormality were recorded. Results: Eighty‐one cats were included (47 unilateral, 34 bilateral bypass systems). Median preoperative renal pelvic diameter was 9 mm (range 3 to 28 mm) and median renal pelvic diameter at the first postoperative ultrasound was 3 mm (range 2 to 23 mm). The median number of postoperative imaging studies was two (range 1 to 8) and the median follow‐up period after surgery was 205 days (range 1 to 1378 days). Bypass system abnormalities were identified postoperatively in 43 (53%) cats, including nephrostomy or cystostomy catheter blockage due to an undetermined cause or kinking of the catheter, nephrostomy or cystostomy catheter leakage, non‐obstructive kinking of the catheter and loose nephrostomy pig‐tail loop. Many abnormalities required repeat surgery, but others were managed conservatively. Fifty‐four percent of obstructed ureters became patent after bypass placement, although the majority remained slightly dilated or had irregular margins compatible with chronic inflammation. Clinical Significance: Bypass abnormalities, mainly tube blockage, occurred frequently in cats treated for ureteral obstruction. Ultrasonography and fluoroscopy were useful for postoperative examination, including documenting renewed ureteral patency and investigation of suspected abnormalities.